Agama tradisional : potret kearifan hidup masyarakat Samin dan Tengger - Nurudin, 1970-; Vina Salviana D. S. (Vina Salviana Darvina Sudarwo), 1962-; Faturrohman, Deden, 1965- (Yogyakarta : LKiS Yogyakarta, 2003)
Sociocultural conditions of Samin people in Blora and Tengger people in Probolinggo; collection of articles
Includes bibliographical references and index
Keywords: Ethnology -- Indonesia -- Java; Tenggerese (Indonesian people); Java (Indonesia) -- Religion